Development and validation of an ecological, new and rapid stability-indicating High Performance Liquid Chromatographic method for quantitative determination of aztreonam in lyophilized powder for injection - Figueiredo, Andressa Leme; Kogawa, Ana Carolina; Salgado, Hérida Regina Nunes (Drug Analytical Research, 2026)
Aztreonam is a monocyclic synthetic antimicrobial with bactericidal activity against Gram-negative bacteria, the first agent from the monobactam family to be therapeutically approved. It was developed and validated analytical method using high performance liquid chromatography with UV detection at 292 nm to quantify the aztreonam. Furthermore, assessing stability through stress tests was carried out. The chromatographic separation was carried out by reverse phase on an Agilent C18 column (250 x 4.6 mm, 5 µm) with a mobile phase composed of water:ethanol (70:30, v/v) adjusted to pH 2.5 with acetic acid, pumped isocratically at a flow rate of 0.5 mL/min. The validation parameters linearity, selectivity, precision, accuracy, robustness, limits of detection and quantification were determined. The method proposed provides linear response within the concentration range of 45-95 µg/mL for aztreonam. Results obtained were found to be satisfactory. The proposed method is linear, accurate, precise, selective, and robust being able to quantify the aztreonam in raw material and in pharmaceutical preparations. The validated method was suitable for applications in quality control laboratories.